Influence Of Instagram Advertising On Millenial Purchase Intention - PA. Andiena Nindya Putri; Mutiara Shifa; I Nyoman Tri Sutaguna; Slamet Maryoso; Arief Yanto Rukmana (International Journal of Management Research and Economics, 2023)
The study aims to analyze the factors that influence the effectiveness of advertising on Instagram and its impact on the buying interests of the Millennial Generation. The factors used are: Credibility, Value, Informative, Emotion, and Entertainment. The analysis was carried out using confirmatory factor analysis based on data collected through cousions adopted from previous research. Data was then analyzed using the SmartPLS statistical program. Significant influences were found on the credibility, informative, emotion, and social media advertising factors. The results of this research can be useful for entrepreneurs who will do advertising on Instagram and also be a reference for students who take digital marketing or consumer behavior courses.